Maya Index Analysis of Dengue Fever Vector in East Metro Sub-District Lampung Province Indonesia - Betara Sona; Emantis Rosa; M. Kanedi; Tugiyono Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
Dengue fever was one of the dangerous diseases due to it might cause death in a short time. It transmitted through its vectors, namely, Aedes aegypti and Aedes albopictus. Maya index is an indicator that used to identify a high-risk area or not as a breeding ground for Aedes sp. The purpose of this study was to determine the type of landfill which has the potential as a breeding ground for mosquitoes, to find out the larvae found in various landfill sites, and to know the Maya index status in Metro Timur Subdistrict which was carried out in November-December 2017. This research conducted by a direct survey of 100 residents' houses in East Metro. The results indicated that the type of controlled water reservoir that had the most potential as a breeding place for mosquitoes was a bathtub, while the type of water reservoir that was not controlled which had the potential as a place for mosquito breeding was a fish pond usage. There were 2 types of larvae found, namely, Aedes aegypti larvae with a percentage of 47.7% and Aedes albopictus larvae with a percentage of 52.3%. The Maya index status detected there, was a medium category, which obtained from the BRI combination and HRI category. Besides, it did not mean that the area has been free from dengue cases. The role of the community is still very much needed in eradicating landfills which has the potential as a breeding place for dengue mosquitoes vector.